Osteonecrosis of the jaw in patients treated with denosumab for metastatic tumors to the bone: A series of thirteen patients. Issue 3 (March 2016) - Owosho, Adepitan A.; Blanchard, Ariel; Levi, Lauren; Kadempour, Arvin; Rosenberg, Haley; Yom, SaeHee K.; Farooki, Azeez; Fornier, Monica; Huryn, Joseph M.; Estilo, Cherry L.
Abstract: This case series describes the course of osteonecrosis of the jaw (ONJ) in thirteen patients with metastatic bone tumors treated solely with denosumab. Patients on denosumab may be more prone to developing ONJ even without a risk/precipitating factor and they may develop ONJ early in their denosumab therapy. The outcomes of ONJ in ten patients following a period of denosumab discontinuation after the onset of ONJ were: 3 had complete resolution of symptoms, 4 patients' ONJ progressed, 2 patients' ONJ was unchanged and in 1 patient there was partial ONJ resolution. The role of drug discontinuation prior to an invasive dental procedure or after the onset of ONJ still remains debatable.